Virtual reality technology enhances the cognitive and social communication of children with autism spectrum disorder - Junqiang Zhao; Junqiang Zhao; Junqiang Zhao; Xinxin Zhang; Xinxin Zhang; Xinxin Zhang; Yi Lu; Yi Lu; Yi Lu; Xingyang Wu; Xingyang Wu; Xingyang Wu; et al. (Frontiers in Public Health, 2022)
ObjectiveWe aimed to explore the impact of using virtual reality technology to intervene in and encourage the developmental behavior areas of cognition, imitation, and social interaction in children with autism spectrum disorder.MethodsForty-four children with autism spectrum disorder were divided randomly into an intervention group and a control group, with each group consisting of 22 participants. Incorporating conventional rehabilitation strategies, virtual reality technology was used with the intervention group to conduct rehabilitation training in areas including cognition, imitation, and social interaction. The control group was provided conventional/routine clinical rehabilitation training. The children's cognitive development was evaluated before and 3 months after intervention.ResultsAfter intervention, the developmental abilities of both groups of children in the areas of cognition, imitation, and social interaction were improved over their abilities measured before the intervention (P < 0.05). However, post-intervention score differences between the two groups demonstrated that the intervention group levels were better than the control group levels only in the areas of cognition and social interaction (P < 0.05).ConclusionCombining virtual reality with conventional rehabilitation training improved the cognitive and social development of children with autism spectrum disorder and supported the goal of improving the rehabilitation effect.